The relationship between response dynamics and the formation of confidence varies across the lifespan - Overhoff, Helen; Ko, Yiu Hong; Fink, Gereon R.; Stahl, Jutta; Weiss, Peter H.; Bode, Stefan; Niessen, Eva (Frontiers in Aging Neuroscience, 2022)
Accurate metacognitive judgements, such as forming a confidence judgement, are crucial for goal-directed behaviour but decline with older age. Besides changes in the sensory processing of stimulus features, there might also be changes in the motoric aspects of giving responses that account for age-related changes in confidence. In order to assess the association between confidence and response parameters across the adult lifespan, we measured response times and peak forces in a four-choice flanker task with subsequent confidence judgements. In 65 healthy adults from 20 to 76 years of age, we showed divergent associations of each measure with confidence, depending on decision accuracy. Participants indicated higher confidence after faster responses in correct but not incorrect trials. They also indicated higher confidence after less forceful responses in errors but not in correct trials. Notably, these associations were age-dependent as the relationship between confidence and response time was more pronounced in older participants, while the relationship between confidence and response force decayed with age. Our results add to the notion that confidence is related to response parameters and demonstrate noteworthy changes in the observed associations across the adult lifespan. These changes potentially constitute an expression of general age-related deficits in performance monitoring or, alternatively, index a failing mechanism in the computation of confidence in older adults.